Chemiluminescence from recombinant spider silk under thermo-oxidative degradation. (October 2017) - Nakayama, Koyuru; Dao, Anh T.N.; Takeuchi, Kengo; Shimokata, Jun'ichi; Taniike, Toshiaki
Abstract: In this work, the oxidative degradation of recombinant spider silk in a solid state was studied based on chemiluminescence analysis. It was found that the chemiluminescence behavior of the recombinant spider silk closely resembled that of aliphatic polyamide: The emission developed without any induction time, and the maximum intensity was observed in the range of 480–520 nm. In combination with infrared spectroscopy, it was concluded that the oxidative degradation of the recombinant spider silk initiates mainly through the hydroperoxide formation at the Cα position of amino acid residues, and its unimolecular decomposition produces imide or α-keto amide groups together with the CL emission.